Pattern of changes in local and global muscle thickness among individuals with sacroiliac joint dysfunction - Joseph,L.H. (Hong Kong Physiotherapy Association, 2015)
© 2015 . Background: Altered motor patterns of the local muscle system (LS) and global muscle system (GS) is reported among low back pain patients. However, the pattern of changes in the LS and GS among individuals with sacroiliac joint dysfunction (SJD) is not clear. Objective: This study aimed to investigate the changes in the resting muscle thickness of LS and GS in SJD. Methods: A total of 40 individuals (20 participants with SJD and 20 healthy participants as matched controls) participated in this study. The resting thickness of the LS and GS such as rectus abdominis (RA), external oblique (EO), internal oblique (IO), transverses abdominis (TrA), and lumbar multifidus (LM) was measured using real time ultrasonography and the data were compared between the ipsilateral side and contralateral side among participants with SJD as well as healthy participants. Parametric and nonparametric statistics were used to analysethe data as appropriate. Results: The results showed that EO and IO were significantly reduced among SJD participants when compared with the contralateral side. Similarly, EO and LM were significantly reduced among the SJD group when compared with the controls. Conclusion: The findings of the study support a trend of reduced size in the resting thickness of the LS and GS in SJD.